Huaytapallana, arte rupestre de Chachapoyas - Ruiz Estrada, Arturo (2010)
The territory of Chachapoyas preserves important archaeological remains among which there are towns, cemeteries, terraces and roads. There are also several examples depicting rock art, which have been known gradually. The current paper presents information that contributes to the knowledge of a new site and tries to describe and understand the nature and meaning of rock art in Huaytapallana, located in the district of Huancas, province of Chachapoyas, Amazonas region, Peru.